EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN MEDIA GAME INTERAKTIF DIGITAL WORDWALL UNTUK MENINGKATKAN INTERAKSI SOSISAL SISWA KELAS IV SD NEGERI PRAWIT 1 SURAKARTA TAHUN 2026 - Sukmawati Dewi, Pingky; Adi Putro , Eko; Dwi Sholikhah, Linda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effectiveness of group guidance services using Wordwall digital interactive games in improving the social interaction of fourth-grade students at SD Negeri Prawit 1 Surakarta. The research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The population consisted of 58 fourth-grade students. The sample was selected through purposive sampling, resulting in 30 students with low to moderate levels of social interaction, who were divided into an experimental group and a control group, each consisting of 15 students. The research instrument was a questionnaire that had been tested for validity and reliability, supported by interviews, observations, and documentation. The data were analyzed using normality, homogeneity, and t-test analyses. The results showed that the experimental group experienced a greater improvement in social interaction scores compared to the control group. The pretest and posttest results indicated a significant difference, as shown by the Independent Samples t-test (Sig. (2-tailed) = 0.046 < 0.05 and the Paired Samples t-test (Sig. (2-tailed) < 0.001 < 0.05. These findings indicate that group guidance services using Wordwall digital interactive games are effective in improving students’ social interaction. Keywords: group guidance, Wordwall, social interaction.